Programer's Guidebook for Cross Country Canada`s Skill Development Program for children (Cross Country Canada, 2009)
CONTENTS 1. Introduction 1.1 CCC's Skill Development Program for Children (SDP) - Bunnyrabbit Program - Jackrabbit Program - Track Attack Program 2. Registration 2.1 Organizational Roles - Cross Country Canada - Your Division - Your Club 2.2 Your Fall Start-Up Kit 2.3 Registration Steps 2.4 Ordering Materials and Supplies 3. SDP Awards System 3.1 Bunnyrabbit Program - Paw Print Sticker - Skill Award Sticker 3.2 Jackrabbit Program - Technique Award Stickers - Program Award Stickers (Snow Goals; Sprints, Hat Tricks) 3.3 Track Attack Program - Incentive Cards 4. SDP Support Structure 4.1 The Support Structure 4.2 Your Ideal Club 4.3 Infrastructure of a Full Service Club 4.4 Role of the Club Head Coach 4.5 The Parent 5. SDP Appendices 5.1 Coaches Code of Conduct 5.2 Parents Code of Conduct 5.3 Facility Safety Checklist 5.4 Athlete Development Grid 5.5 Season Plan Chart 5.6 Fundamental Skills Checklist Levels 1-4 5.7 Progress Report Form